K-Uniformly Multivalent Functions Involving Liu-Owa Q-Integral Operator - ÇETİNKAYA, ASENA (Scientific and Technological Research Council of Turkey, 2021)
In this paper, we introduce q-analogue of Liu-Owa integral operator and define k-uniformly multivalent starlike functions of order gamma, (0 <= gamma < p; p is an element of N) by using Liu-Owa q-integral operator. We examine coefficient estimates, growth and distortion bounds for the functions belonging to the subclass of k-uniformly multivalent starlike functions of order gamma. Moreover, we determine radii of k- uniformly starlikeness, convexity and close-to-convexity for the functions belonging to this subclass.
k-uniformly multivalent functions involving Liu-Owa q-integral operator
Keywords: Analytic Functions; Starlike Functions; Growth Theorem; Distortion Theorem; Coefficient Estimate